Influence of beta(S) allele in the lipid peroxidation and antioxidant capacity parameters - Shimauti, E. L. T. [UNESP]; Belini Junior, E. [UNESP]; Baracioli, L. M. da S. V. [UNESP]; Souza, E. M. de; Granzotto, D.; Almeida, E. A. de [UNESP]; Silva, D. G. H. [UNESP]; Ricci Junior, O.; Bonini-Domingos, C. R. [UNESP] (Wiley-Blackwell, 2014)
Introduction: The oxidative process plays a fundamental role in the pathophysiology of sickle cell anemia (SCA), and population and environmental characteristics may influence redox balance. The aim of this study was to evaluate lipid peroxidation and antioxidant capacity in Brazilian Hb S carriers undergoing different therapies.MethodsBlood samples from 270 individuals were analyzed (Hb SS, n=68; Hb AS, n=53, and Hb AA, n=149). Hemoglobin genotypes were assessed through cytological, electrophoretic, chromatographic, and molecular methods. Plasma lipid peroxidation and antioxidant capacity were measured by spectrophotometric methods.ResultsPatients with SCA who used iron-chelating drugs combined with hydroxyurea, associated with regular transfusions, showed lower levels of TBARS (P <= 0.05), higher levels of TEAC (P <= 0.01), and lower TBARS/TEAC ratio (R=255.8). The redox profile of Hb AS subjects was not statistically different (P>0.05) from that of Hb AA subjects.ConclusionThe data suggest that oxidative stress is lower in the patients with SCA who received regular blood transfusions associated with the combined use of HU and iron chelators than the group received only HU. The redox system of the Hb AS carriers is compatible with the control group.
Keywords: Oxidative stress; Sickle cell anemia; TBARS; TEAC; Sickle cell trait